HUBUNGAN PERAN KEPEMIMPINAN KEPALA RUANGAN DENGAN KINERJA PERAWAT PELAKSANA DI MURNI TEGUH MEMORIAL HOSPITAL - Pardede, Lena M.; Sagala, Lam Murni (Indonesian Trust Nursing Journal, 2025)
Nurse performance is the answer to the quality of nursing services provided to patients during treatment. One of the problems related to the performance of nurses is the implementation of nursing care that is not in accordance with the goals set by the hospital. For inpatient room nurses, the head of the room is a leader who can move nurses to be able to carry out their performance well. The objective of this study is to determine the relationship between the leadership role of the head of the room with the performance of the implementing nurse. This research method is quantitative research with cross sectional approach. The sample is 66 people and used proportional sampling technique. The analysis was carried out univariate and bivariate using the spearman's rho rank test with a 95% confidence level ( = 0.05). This study shows that the leadership role of the head of the room according to the implementing nurse is in the good category (53.0%). The performance of the implementing nurse was in the good category (54.5%). The leadership role of the head of the room was significantly related to the performance of nurses, p-value = 0.000 <0.05, with a close relationship (correlation coefficient) of the two variables of 0.747 (high). It is concluded that the performance of implementing nurses at Murni Teguh Memorial Hospital is related to the role of leadership. It is recommended that further researchers to add variables such as work motivation, teamwork, and others.